2018
DOI: 10.1016/j.omtn.2018.02.001
|View full text |Cite
|
Sign up to set email alerts
|

Cryptotanshinone Protects Cartilage against Developing Osteoarthritis through the miR-106a-5p/GLIS3 Axis

Abstract: Cryptotanshinone (CTS) has emerged as an anti-inflammatory agent in osteoarthritis (OA). However, the molecular mechanism underlying its potent therapeutic effect on OA remains largely unknown. MicroRNAs (miRNAs) act as crucial regulators in maintaining cartilage homeostasis. To investigate whether CTS protects against developing OA through regulation of miRNAs, we examined the potential CTS-mediated miRNA molecules using microarray analysis. We found that CTS significantly promoted miR-106a-5p expression in c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 51 publications
0
21
0
Order By: Relevance
“…Chondrocytes are solely responsible for the synthesis of ECM components 5 , 58 . However, cartilage cellularity is reduced in OA, and the remaining chondrocytes are activated by various cytokines to express a catabolic and abnormal phenotype with poor proliferation and migration potential, resulting in accelerated degradation and limited capacity of the ECM for self-repair and regeneration 3, 4, 5 , 21 .…”
Section: Discussionmentioning
confidence: 99%
“…Chondrocytes are solely responsible for the synthesis of ECM components 5 , 58 . However, cartilage cellularity is reduced in OA, and the remaining chondrocytes are activated by various cytokines to express a catabolic and abnormal phenotype with poor proliferation and migration potential, resulting in accelerated degradation and limited capacity of the ECM for self-repair and regeneration 3, 4, 5 , 21 .…”
Section: Discussionmentioning
confidence: 99%
“…MiR dysregulation has been implicated in different diseases (Farooqi et al, 2019; Lu, Weng, Li, Yang, & Qian, 2020). Administration of CT upregulates the expression of miR‐106a‐5p to inhibit GLI‐similar 3 (GLIS3), resulting in amelioration of osteoarthritis (Ji et al, 2018). Dual modulation of NF‐κB and Nrf2 signaling pathways lead to excellent anti‐inflammatory activity of CT (Li et al, 2020).…”
Section: Cryptotanshinone: An Overview Of Its Therapeutic Activitiesmentioning
confidence: 99%
“…Administration of CT upregulates the expression of miR-106a-5p to inhibit GLI-similar 3 (GLIS3), resulting in amelioration of osteoarthritis (Ji et al, 2018). Dual modulation of NF-κB and Nrf2 signaling pathways lead to excellent anti-inflammatory activity of CT .…”
Section: Effect On Molecular Pathwaysmentioning
confidence: 99%
“…As a highly prevalent disease, osteoarthritis is a considerable burden to public health. Despite several decades of investigation, there is still no effective therapeutic agents for OA treatment [39]. Our study demonstrated that HMGB1 can exert dual effects on inflammatory reaction based on its locations in chondrocytes.…”
Section: Discussionmentioning
confidence: 64%